Increasing Public Understanding of the Prevention and Complaints of Fraudulent Investments - Suprapti, Duhita Driyah; Fibrianti, Nurul; Maharani, Anggun Meinanda (Indonesian Journal of Advocacy and Legal Services, 2022)
The many offers of high income make many people interested in investing. People's carelessness backfires on those who are victims of fraudulent investments. Illegal investment or more commonly known as a fraudulent investment is indeed carrying out investment activities that are not following existing regulations. The ease of access to information and the affordability of technology today has become the ground for illegal investment actors to look for victims. Investments that initially aim to obtain maximum income from existing capital in the future harm investors. In illegal assets, it is not only the activities that are not appropriate, but the completeness of the licensing documents for investment companies is also incomplete. Many types of activities resemble investments but are fake or illegal. The victims of this activity are not only a few. Even from all walks of life are victims of this irresponsible activity. This service is carried out by educating the public regarding complaints and assisting with illegal investments. This service will be carried out by providing investment training for the community in Kalipancur Village, especially for mothers and teenagers who are often the target of investment fraud. Such an approach is expected to provide validity of the results as a good outcome. This training is considered efficient and effective because the public understands and understands commercial transactions through the internet to increase their knowledge to increase their income and standard of living.